First reported outbreak of green tobacco sickness in Brazil Primeiro relato do surto da doença da folha verde do tabaco no Brasil - Patricia Pereira Vasconcelos de Oliveira; Camila Brederode Sihler; Lenildo de Moura; Deborah Carvalho Malta; Maria Célia de Albuquerque Torres; Sandra Márcia da Costa Pereira Lima; Ana Lucia Alves de Lima; Carlos Eduardo Leite; Vera Luiza da Costa-; Jeremy Sobel; Tatiana Miranda Lanzieri (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
Dermal absorption of nicotine by people harvesting tobacco may cause an acute intoxication called green tobacco sickness. Although Brazil is the second largest producer of tobacco in the world, green tobacco sickness had not been reported in the country to date. We conducted a 1:1 matched case-control study among persons involved in tobacco farming to determine the occurrence of green tobacco sickness in the northeast region of Brazil and to identify the risk factors involved. A case-patient was a person who received a diagnosis by health professional of acute intoxication during the study period and had a cotinine level over 10ng/mL detected by High Performance Liquid Chromatography. We identified 107 case-patients. The main signs and symptoms observed were dizziness, weakness, vomit, nausea and headache. Independent risk factors identified were being male, a non smoker and having worked in the harvest of tobacco leaves. Case-patients had higher median urinary cotinine levels than controls (p < 0.05). Epidemiological and laboratory data indicate for the first time the occurrence of green tobacco sickness in Brazil. A absorção dérmica da nicotina por agricultores que trabalham com o cultivo do tabaco provoca uma intoxicação aguda denominada doença da folha verde do tabaco. Apesar de o Brasil ser o segundo produtor mundial de tabaco, a doença da folha verde do tabaco ainda não havia sido relatada no país. Conduzimos um estudo de caso-controle pareado (1:1) entre pessoas envolvidas na cultura do tabaco para determinar a ocorrência de doença da folha verde do tabaco na Região Nordeste do Brasil e identificar fatores de risco. Um paciente-caso foi a pessoa que no período de estudo foi diagnosticada de intoxicação aguda por profissionais de saúde e teve nível de cotinina acima de 10ng/mL pela Cromatografia Líquida de Alta Eficiência. Identificamos 107 pacientes-caso. Principais sinais e sintomas observados foram tontura, fraqueza, vômito, náusea e cefaléia. Foram associados ao adoecimento ser do sexo masculino, não-fumantes e ter trabalhado na fase da colheita do tabaco. A mediana de cotinina urinária entre os pacientes-caso foi maior que os controles. Os dados epidemiológicos e laboratoriais confirmaram pela primeira vez a doença da folha verde do tabaco no Brasil.